Social representations attributed to prostate cancer by men undergoing follow-up at an in-hospital Oncology service - Bianca de Moura Peloso-Carvalho; Rogério Silva Lima; José Vitor da Silva; Namie Okino Sawada; Eliza Maria Rezende Dázio; Murilo César do Nascimento; Silvana Maria Coelho Leite Fava (Universidade Federal do Ceará, 2023)
Objective: to understand the social representations of prostate cancer by men undergoing follow-up at an in-hospital oncology service. Methods: a qualitative study, developed using the Collective Subject Discourse method, with 30 men over the age of 18 undergoing treatment for prostate cancer. The data were collected through semi-structured interviews and analyzed using the Theory of Social Representations. Results: the most shared central ideas in the studied community were as follows: A curable disease; Worry, fear, annoyance and sadness; Loss/Impairment of sex; Nothing, something normal/common; A minor ailment that doesn't shake/shook me, it was faced head on, without fear; Something/Disease that is bad, difficult, serious, intense, dangerous, that ends life and kills. Conclusion: the social representations found in this study denoted intense and difficult experiences in dealing with the disease and treatment, but also showed coping, with potential for overcoming/resilience. Contributions to practice: understanding these representations enables the implementation of integrated and interprofessional education, assistance and management actions.